2005
DOI: 10.1038/nature04150
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a protochordate histocompatibility locus

Abstract: Histocompatibility--the ability of an organism to distinguish its own cells and tissue from those of another--is a universal phenomenon in the Metazoa. In vertebrates, histocompatibility is a function of the immune system controlled by a highly polymorphic major histocompatibility complex (MHC), which encodes proteins that target foreign molecules for immune cell recognition. The association of the MHC and immune function suggests an evolutionary relationship between metazoan histocompatibility and the origins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
193
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(194 citation statements)
references
References 29 publications
0
193
0
1
Order By: Relevance
“…Notably, despite the apparent absence of MHC molecules, Botryllus schlosseri (a colonial protochordate) 142 and Hydractinia species (cnidarians; which are invertebrates) 143,144 show HISTOCOMPATIBILITY REACTIONS (that is, allotransplantation reactions) through a process known as fusibility, which protects the germline by inhibiting chimerism and/or parasitism 145 . Fusibility is determined by a single Mendelian trait and, in Botryllus schlosseri 146 , is mediated by highly polymorphic cell-surface receptors that contain immunoglobulin-superfamily and epidermal-growth-factor domains that are encoded at a single locus 147 . Notably, again, a chimeric structure is involved in an immune-type function.…”
Section: Box 1 Alternative Mediators Of Histocompatibilitymentioning
confidence: 99%
“…Notably, despite the apparent absence of MHC molecules, Botryllus schlosseri (a colonial protochordate) 142 and Hydractinia species (cnidarians; which are invertebrates) 143,144 show HISTOCOMPATIBILITY REACTIONS (that is, allotransplantation reactions) through a process known as fusibility, which protects the germline by inhibiting chimerism and/or parasitism 145 . Fusibility is determined by a single Mendelian trait and, in Botryllus schlosseri 146 , is mediated by highly polymorphic cell-surface receptors that contain immunoglobulin-superfamily and epidermal-growth-factor domains that are encoded at a single locus 147 . Notably, again, a chimeric structure is involved in an immune-type function.…”
Section: Box 1 Alternative Mediators Of Histocompatibilitymentioning
confidence: 99%
“…We showed that this primitive immune response was controlled by a single highly polymorphic locus or haplotype (177). The rules of fusion or rejection follow those of NK recognition of self, wherein sharing a single allele halts the effector immune reactions that occur between zooids or colonies that do not share an allele at the locus (177)(178)(179)(180).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…Selon la vision traditionnelle fondée sur la morphologie comparée, l'histoire évolutive des Deutérostomiens est interprétée comme une marche progressive vers la complexité allant des formes « simples » vers les formes plus « complexes », lesquelles « culminent » Ainsi, la récente découverte d'un locus d'histocompatibilité chez l'Ascidie coloniale, Botryllus schlosseri, nous plonge directement aux origines de notre système immunitaire [8] tout en nous permettant de mieux comprendre le fonctionnement des cellules souches [9]. Comptant parmi les organismes producteurs de molé-cules aux propriétés anti-tumorales [10], les Tuniciers constituent, en outre, un réservoir potentiel de biomolécules naturelles qui ne demande qu'à être exploré.…”
unclassified